EFEKTIVITAS PROGRAM PERLINDUNGAN SOSIAL DALAM MENGURANGI KEMISKINAN MULTIDIMENSI - Sarkila, Agung Putra; Muliawan, Muliawan; Fadilah, Ana Ananta (Visi Pencerah Nusantara, 2024)
This study aims to assess the effectiveness of social protection programs in reducing multidimensional poverty by emphasizing the importance of sensitivity to local context and intersectionality. The Systematic Literature Review (SLR) approach is used to critically examine research results from the Dimensions and Scopus databases over the past five years (2020–2025). The analysis focuses on studies that explicitly discuss the impact of social protection on non-monetary dimensions of poverty, taking into account regional, gender, age differences, and structural factors that influence implementation. The results show that although social protection programs contribute significantly to reducing deprivation, their effectiveness is greatly influenced by program design, targeting mechanisms, and adaptation to the specific needs of vulnerable groups. The gap between design and implementation, as well as the lack of integration of gender-based and contextual approaches, are key challenges. This study recommends developing policies based on microregional data that are responsive to local and social dynamics, to ensure more inclusive and sustainable interventions. The findings provide conceptualization and practicality for policymakers in designing equitable and evidence-based social interventions.